Consanguinidad y parentesco político en el ámbito de los puertos, barcos, sus propietarios y conexiones. Cádiz-Buenos Aires y el territorio rioplatense : siglos XVIII-XIX - Nora Siegrist de Gentile (Centre de Recherches sur les Mondes Américains, 2016)
The topic of the matriculated Cadiz settlers and of those who went to Hispanic America has long been object of study, but there are still open questions as to their destination. This paper focuses on the Cargadores a Indias who arrived in the River Plate by using the connection between the southern ports of Spain and the ports of America. The arrangements of the settlers – or of those who stayed only for a period – have strict relationships, from the point of view of their kinship and their social and economic frameworks, in both continents. This study also shows a direct participation of the Third Order of Saint Francis in the extended Buenos Aires city, and in the River Plate territory.